Tuning magnetic properties in layered metal-organic frameworks - Pitcairn, Jem (2024)
This thesis explores the role of chemistry and structure in the magnetic properties of metal-organic framework materials. New magnetic materials with enhanced properties are promising for next-generation information technology with higher speeds, energy efficiency and data density. Realising these new technologies calls for programmable materials where the magnetic properties can be tuned by controlling the chemical composition and crystal structure. Metal-organic magnets (MOMs), assembled from metal nodes connected by organic molecular linkers into extended networks, offer these benefits. The modularity of their construction allows for the tuning of magnetic properties by substituting the nodes and linkers while retaining network topology. The chemical and structural complexity of these materials makes predicting their magnetic properties challenging. Developing this understanding requires deeper exploration of the influence chemistry and structure have on the magnetism in new MOMs.